Evaluation of Etest and MICRONAUT-AM Assay for Antifungal Susceptibility Testing of Candida auris: Underestimation of Fluconazole Resistance by MICRONAUT-AM and Overestimation of Amphotericin B Resistance by Etest - Mohammad Asadzadeh; Suhail Ahmad; Wadha Alfouzan; Inaam Al-Obaid; Bram Spruijtenburg; Eelco F. J. Meijer; Jacques F. Meis; Eiman Mokaddas (Antibiotics)
Multidrug-resistant Candida auris has recently caused major outbreaks in healthcare facilities. Rapid and accurate antifungal susceptibility testing (AST) of C. auris is crucial for proper management of invasive infections. The Commercial Sensititre Yeast One and Vitek 2 methods underestimate or overestimate the resistance of C. auris to fluconazole and amphotericin B (AMB). This study evaluated the AST results of C. auris against fluconazole and AMB by gradient-MIC-strip (Etest) and broth microdilution-based MICRONAUT-AM-EUCAST (MCN-AM) assays. Clinical C. auris isolates (n = 121) identified by phenotypic and molecular methods were tested. Essential agreement (EA, ±1 two-fold dilution) between the two methods and categorical agreement (CA) based on the Centers for Disease Control and Prevention’s (CDC’s) tentative resistance breakpoints were determined. Fluconazole resistance-associated mutations were detected by PCR-sequencing of ERG11. All isolates identified as C. auris belonged to South Asian clade I and contained the ERG11 Y132F or K143R mutation. The Etest–MCN-AM EA was poor (33%) for fluconazole and moderate (76%) for AMB. The CA for fluconazole was higher (94.2%, 7 discrepancies) than for AMB (91.7%, 10 discrepancies). Discrepancies were reduced when an MCN-AM upper-limit value of 4 µg/mL for fluconazole-susceptible C. auris and an Etest upper-limit value of 8 µg/mL for the wild type for AMB were used. Our data show that resistance to fluconazole was underestimated by MCN-AM, while resistance to AMB was overestimated by Etest when using the CDC’s tentative resistance breakpoints of ≥32 µg/mL for fluconazole and ≥2 µg/mL for AMB. Method-specific resistance breakpoints should be devised for accurate AST of clinical C. auris isolates for proper patient management.